Expanding Remote Patient Monitoring for Pre‐Lung Transplant Candidates With Interstitial Lung Disease - Lisa Wickerson; Tamires De Mori; Noori Chowdhury; Cecilia Chaparro; Nikki Marks; Shaf Keshavjee; Aman Sidhu (Clinical Transplantation, 2026)
ABSTRACT Introduction Interstitial lung disease (ILD) is a primary indication for lung transplantation (LTx). Close monitoring of disease progression informs transplant urgency, timing, medical and pre‐habilitation management, and remote home monitoring may support frequent assessment of clinical status and response to interventions. Methods LTx candidates with ILD received a home spirometer, pulse oximeter, and activity tracker. Participants manually entered data weekly and completed the King's Brief ILD questionnaire (KBILD) monthly within a patient portal linked to the electronic medical record (EMR). Results Of 63 people approached at the start of outpatient pre‐habilitation, 50 (79%) enrolled for additional remote monitoring and 40 (80%) entered data for ≥4 weeks. Reporting adherence was higher for pulse oximetry (82%) and spirometry (69%) than daily steps tracking (31%). During a median LTx waiting period of 11 [4–18] weeks, there were no changes in home spirometry or self‐reported health status; however, daily step count decreased (mean 5639 ± 3989–4653 ± 3303; p = 0.04, n = 25). Wait list status for transplant urgency was increased during the study period in 40% of participants. Fraction of inspired oxygen (FiO 2 ) for exertion increased (median 0.49 [0.17]–0.51 [0.16]; p = 0.01), with no clinically significant hypoxemia reported after aerobic exercise. For 20 participants using a treadmill for both on‐site and home exercise, median on‐site walking distance was maintained (912 [469]–966 [497] m; p = 0.64), whereas home‐based walking distance declined (1073 [831]–1019 [409] m, p = 0.02). Conclusion Remote monitoring in LTx candidates with ILD was feasible, with data integrated into the EMR for clinicians to view. This can provide multimodal data to inform clinical status changes and interventions. Future plans include direct device (Wi‐Fi, Bluetooth) integration of monitoring tools into the EMR to increase reporting and decrease manual entry errors, and building escalation alerts for changes in spirometry, oximetry, and activity.